Breast cancer trends in women in Cyprus: a population-based study between 2004-2017: Annalisa Quattrocchi. (25th October 2022) - Quattrocchi, A; Demetriou, CA; Cory, OA; Saad, B; Constantinou, C; Marcou, Y; Demetriou, A; Scoutellas, V; Kolokotroni, O
Abstract: Background: In Cyprus, breast cancer (BC) is the first in incidence and second in mortality cancer in women. A national screening programme (NSP), targeting women 50-69 years, was introduced in 2007. The aim of this study is to provide a better understanding of cancer trends. Methods: Data from the national population-based Cyprus Cancer Registry on adult women diagnosed with BC between 2004-2017 with follow-up until 2019 were analysed as follows: Joinpoint regression for age-adjusted (overall and by tumor stage at diagnosis - TSD) and age-specific rates (<50, 50-59, 60-69, 70-79, ≥ 80) incidence and mortality rates; 5-year age-adjusted Net Survival (NS) rates, overall and by TSD. TSD was categorised as localised, regional, and distant. Results: Age-adjusted incidence rate increased from 135.3 (2004) to 153.2 (2017) per 100, 000, with an annual percentage change (APC) of 1.1% (95%CI: 0.4-1.9). The greatest increase was in the age groups ≥70 years. A positive time trend was found for localized cancers between 2006-2017, while for all other stages nonsignificant trends were detected. Age-adjusted mortality rate increased from 37.0 (2004) to 50.0 (2019) per 100, 000 (APC: 2.7%; 95%CI: 1.9-9.4). Significant increases in mortality rates were detected in the age groups ≥70 years. By TSD, increased rates were found at localised and regional stages, however smaller increases were detected since 2007. NS rates for the most recent period (2014-2017) was 93% for localized, 81% for regional, and 32% for distant and did not significantly improve compared to the previous years. Conclusions: Trends in BC incidence continues to increase, especially in the older age groups and for early-stage cancers. As expected, since the introduction of the NSP, the incidence of localised cancers increased whilst the incidence of advanced stage cancer decreased, albeit non-significantly. Survival trends did not change but mortality rates for localised and regional cancers increased at a slower pace. Key messages:  The introduction of the national screening programme may have played an important role in the increasing BC incidence trends.  Despite survival rates not improving since the introduction of the national screening programme, mortality rates for early-stage cancers show a less steep increase.